Announcements (The Review of Asset Pricing Studies, 2017)
Journal Article Announcements Get access The Review of Asset Pricing Studies, Volume 7, Issue 2, December 2017, Page 171, https://doi.org/10.1093/rapstu/rax022 Published: 13 November 2017